A numerical analysis for some non-linear constitutive problems in solid mechanics - Nhu, Ngo Huong (Vietnam Journal of Mechanics, 2004)
The paper deals with the application FEM for solving nonlinear constitutive problems in solid mechanics. The basis equations and algorithms of iterative processing are presented. Some programs written by languages Gibian and special operators in Castem 2000 are established. The problem for the spherical shell made of elasto-plastic material subjected to monotone increasing pressures is solved and calculated results are compared with the theoretical solution and give a good agreement. The influence of the pressure values on the plastic regions of sphere is investigated. The stress, displacement and plastic deformation states for spherical shell and plate with hollow acted on by complex cyclic loads are considered. These given programs can be applied in other problem with more complex geometry, load and material conditions.